2000
DOI: 10.1002/chin.200034084
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Pd‐Catalyzed Ring Opening of Cyclopropanols.

Abstract: 2000 cyclopropane derivatives cyclopropane derivatives Q 0021 -084Pd-Catalyzed Ring Opening of Cyclopropanols.-In the presence of catalytic Pd-compounds, 1-substituted cyclopropanols (I) and (IV) undergo a ring opening to enones (II) and (V) in good yields.-(OKUMOTO,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 1 publication
1
14
0
Order By: Relevance
“…[20][21][22] A report of the same transformation catalyzed by a broad range of palladium catalysts was disclosed independently by Okumoto. 72 The study of the regioselectivity of the process was limited to one example, which nevertheless confirmed the results obtained with 231.…”
Section: Scheme 44 Rhodium-catalyzed [5+2] Cycloaddition Of Iminessupporting
confidence: 74%
“…[20][21][22] A report of the same transformation catalyzed by a broad range of palladium catalysts was disclosed independently by Okumoto. 72 The study of the regioselectivity of the process was limited to one example, which nevertheless confirmed the results obtained with 231.…”
Section: Scheme 44 Rhodium-catalyzed [5+2] Cycloaddition Of Iminessupporting
confidence: 74%
“…16 Okumoto and co-workers found that this reaction can also be efficiently catalyzed by a number of Pd catalysts, with Pd(dba) 2 (dba = dibenzylideneacetone) giving the desired product 6 in good yield and selectivity (Scheme 2). 17 Under these conditions, the major side-product is the ring-opened ketone resulting from protodemetalation of the Pd homoenolate prior to β-hydride elimination. 1-Substituted and 1,2- disubstituted cyclopropyl alcohols were ring-opened using this methodology.…”
Section: Metal-catalyzed β-Carbon Elimination (Metal Homoenolates)mentioning
confidence: 99%
“…22 In 2018, Dai and co-workers reported a Cu-catalyzed γbutyrolactone and δ-ketoester synthesis from cyclopropyl alcohols, which is thought to proceed via enone intermediates (Scheme 5a). 23 Under Cu catalysis, cyclopropyl alcohols (16) can be treated with α-haloesters (17) to arrive at the γbutyrolactone (18). This reaction is thought to begin by the formation of either a Cu(II) homoenolate (19) or β-keto radical (20) from the cyclopropyl alcohol (16).…”
Section: Metal-catalyzed β-Carbon Elimination (Metal Homoenolates)mentioning
confidence: 99%
“…6 Two catalytic cycles depending on the Pd oxidation state have been proposed (Scheme 1, paths a 7 and b). 8 Reaction of palladium with the O-H bond leads to either 1 A or 1 B. Subsequent cleavage of the C-C bond provides 1 C and 1 D, respectively.…”
Section: Conversion To Enonesmentioning
confidence: 99%